Applied Behavior Analysis (ABA) as a Footprint for Tutoring Systems: A Model of ABA Approach Applied to Olfactory Learning - Michela Ponticorvo (Social Sciences, 2020)
Applied Behavior Analysis (ABA) belongs to the analysis of behavior techniques introduced by the theorists of behaviorism in psychological fields. It deals with the application of behaviorism principles to guide the learning process. It can serve as a footprint to build artificial tutoring systems in environments for specific learning processes. In this paper, we delineate the pathway to build an artificial tutoring system following ABA footprints, named the ABA tutor. In implementing the ABA tutor, the techniques of ABA are reproduced. This paper also describes how to build a tutor based on ABA and how to use it to favor olfactory learning. In more detail, the ABA tutor is inserted in SNIFF, a system that combines a software and a hardware side to assess and practice the sense of smell exploiting gamification. A first experiment was run involving 90 participants, and the results indicated that the artificial tutoring system based on ABA principles can effectively promote olfactory learning. The implications of this approach are discussed.